Analyse et structure du travail - Jean-Marie Faverge (Perspectives Interdisciplinaires sur le Travail et la Santé)
The article by Jean-Marie Faverge, which is reproduced here, was published in the first issue of the Bulletin of the Centre d’Études et de Recherches Psychotechniques (CERP) in 1952. Already, it questioned some of the conceptions of psychotechnics at that time, which are oriented towards the selection and fragmentation of human activity.